BAS/BSCR3 Partial reconstruction of myocardial metabolic pathways following analysis of peripheral serum using metabolomics in early cardiac ischaemia. Issue 17 (26th August 2010) - Mamas, M A; Dunn, W B; Broadhurst, D; Chacko, S; Brown, M; El-Omar, M; Fath-Ordoubadi, F; Goodacre, R; Kell, D B; Neyses, L
Abstract : Cardiac metabolism and cardiac function are inextricably linked, with changes in cardiac metabolism during cardiac ischaemia contributing to the development of cardiac arrhythmias. Using metabolomics, we aim to identify metabolite changes occurring during cardiac ischaemia through analysis of peripheral serum to reconstruct myocardial metabolic pathways that contribute to the development of cardiac arrhythmias. Peripheral venous samples from 25 patients (and 20 patients in a validation cohort) were analysed in an untargeted fashion using LC-MS following cardiac ischaemia induced by transient coronary artery occlusion during PCI at baseline, 1 and 5 min. Following validation, 99 and 126 metabolite peaks were significantly different at 1 min and 5 min after coronary occlusion compared with baseline (p<0.05). Predominantly metabolic pathways involving lipids were perturbed with changes in diacylglycerols (DG), lysophophatidylcholines (LPC), phosphatidylcholine (PC) and free fatty acids (FFA). Myocardial metabolic pathways involving the synthesis of PC from DG and their subsequent breakdown by phospholipase A2 into LPC and FFA such as arachidonic acid (AA) stimulating the oxidation of adrenaline to form the arrhythmogenic metabolite adrenochrome were reconstructed. We are able to reconstruct metabolic pathways involving lipid metabolism within the myocardium during cardiac ischaemia through analysis of the peripheral serum using metabolomics. Our unbiased approach has identified metabolic pathways involved in the production and release of metabolites with pro-arrhythmic properties (AA, LPC and adrenochrome) and metabolites with anti-arrhythmic properties (omega-3 fatty acids: eicosapentaenoic and docosahexanoic acid). This suggests that arrhythmogenesis may be a delicate balance between the endogenous formation of pro-arrhythmic and anti-arrhythmic metabolites.